The family Marcgraviaceae in Paraíba State, Brazil - Stefanny Martins de Souza; Diego Giraldo-Cañas; Erimágna de Morais Rodrigues; José Iranildo Miranda de Melo (Caldasia)
Marcgraviaceae belongs to the order Ericales, has eight genera and about 130−140 species. In Brazil, it is currently represented by six genera and 39 species. This work aimed to carry out the taxonomic survey of the family in the State of Paraíba, Brazilian northeastern. Digitized databases, physical and virtual herbaria were consulted and field visits were made. In the study area three species in three genera were found: Marcgravia coriacea, Schwartzia brasiliensis, and Souroubea guianensis. Marcgravia coriacea and S. guianensis are here recorded for the first time for the flora of the State. Taxonomic descriptions, illustrations, a key to species, geographic distribution data, habitats, and reproductive phenology for the species are presented.